Analisis Perhatian Visual dan Usability Pada Tampilan Website Gramedia Digital Menggunakan Metode Eye tracking - Tsabitah, Laila; Indah, Dwi Rosa; Firdaus, Mgs Afriyan; Lestari, Endang; Gumay, Naretha Kawadha Pasemah (Institut Teknologi Garut, 2025)
The Gramedia Digital website, a digital reading service platform, has been identified as facing usability challenges and visual clarity issues that may hinder efficiency and user experience. Therefore, this study integrates two methods—Eye Tracking using RealEye.io and Usability Testing through Maze.co—to comprehensively evaluate the interface and user interactions. The evaluations conducted via RealEye.io and Maze.co involved five participants who were asked to complete three primary tasks: logging in, browsing book categories, and performing checkout. The results indicate that in Task 1 (Login), the visual focus of all participants was well-directed toward the input fields and action buttons. The usability test showed an average completion time of 15.1 seconds, a misclick rate of 16.7%, and a usability score of 97. In Task 2 (Browsing Book Categories), users’ visual attention was efficiently distributed from the navigation menu to the list of books, with a usability score of 91 and a low misclick rate. Conversely, Task 3 (Checkout) revealed significant challenges, as most participants struggled to locate the “Free Content” menu, resulting in a 67% misclick rate, 40% off-path behavior, and the lowest usability score (59). By combining Eye Tracking and Usability Testing, this study successfully provides a comprehensive overview of users’ visual attention patterns as well as the effectiveness and efficiency of their interactions with the interface.